A Rare Genodermatosis: Lipoid Proteinosis - Özkoca, Defne; Tozakoğlu, Batuhan; Uzunçakmak, Tuğba Kevser; Kutlubay, Zekayi (Cerrahpaşa Medical Journal, 2021)
Lipoid proteinosis is a rare genodermatosis that manifests with hoarseness and cutaneous findings. Its skin manifestations start with vesicles during the neonatal period, later scar formation and lichenification are observed. Beaded papules on the eyelids, which is referred to as “moniliform bleapharosis” is a typical finding. Here, we present a case of this rare disease with the typical manifestations of the disease. Cite this article as: Özkoca D, Tozakoğlu B, Kevser Uzunçakmak T, Kutlubay Z. A rare genodermatosis: Lipoid proteinosis. Cerrahpaşa Med J. 2021;45(3):227-229.